Critical Reflections on Rothbard's Concept of Gross Investment - Eduard Braun (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2013)
This paper critiques Rothbard's ([1962] 2004) concept of gross investment. Rothbard introduced the concept in order to demonstrate his point that it is not consumer spending that primarily drives the economy, like the mainstream Keynesian view maintains, but the capitalists' spending. In this paper, it is argued that, contrary to Rothbard's opinion, the amount of gross investment as he defines it does not contain significant information concerning the question as to whether the capital structure of a society can be upheld or not. Instead, it is an arbitrary figure that depends on the length of the different stages of production. This problem has not been recognized by Rothbard because his exposition rests upon the assumption of an equal time-length for all stages. Apparently, he has been led astray by his intention to find arguments against the importance of consumer spending in the determination of output.
Keywords: B53; E22; E23; 330; Gross Investment; Murray N. Rothbard; Structure of Production